1999
DOI: 10.1161/01.cir.99.22.2858
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Lipoprotein Levels in Fasting Serum Predict Coronary Events in Patients With Coronary Artery Disease

Abstract: Background-Remnant lipoproteins are atherogenic, but assays of remnants have not been available in routine clinical laboratories because of the lack of practical and validated methods. A simple and reliable method for such an assay, using an immunochemical approach, has recently been developed. This study prospectively examined whether remnant lipoprotein levels in fasting serum, measured by our method, may have prognostic value in patients with coronary artery disease (CAD). Methods and Results-Remnant lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
162
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(177 citation statements)
references
References 12 publications
15
162
0
Order By: Relevance
“…Associations of RLP-Clevels with coronary events have recently been reported (24,25). Wehave previously reported that RLP-C levels are markedly high in patients who have established coronary artery stenosis (26).…”
Section: Discussionmentioning
confidence: 96%
“…Associations of RLP-Clevels with coronary events have recently been reported (24,25). Wehave previously reported that RLP-C levels are markedly high in patients who have established coronary artery stenosis (26).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, there are strikingly different RLP‐C levels across studies 10, 27, 28, 43. These differences strongly suggest that the methods used (ie, immunoseparation, ultracentrifugation) have significantly different profiles or sensitivities for separating and measuring remnant lipoproteins.…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective study of 135 patients with coronary artery disease who presented to a hospital in Japan and were followed for up to 3 years, higher RLP‐C levels were an independent predictor of recurrent coronary events 27. A prospective analysis of >1100 older Japanese American men from the Honolulu Heart Study found that RLP levels were independently predictive of incident CHD during 17 years 11.…”
Section: Discussionmentioning
confidence: 99%
“…These remnants are formed after hydrolysis of triglycerides by lipoprotein lipase from intestine-derived chylomicrons, and they are rapidly removed from the circulation. Delayed clearance of these triglyceride-rich lipoprotein particles induced by genetic or metabolic abnormalities is often associated with accelerated atherosclerosis (18,20,21). However, no evidence has yet been found for a connection between chylomicron remnants and PAI-1 production.…”
Section: Lipoproteinsmentioning
confidence: 99%